2023
DOI: 10.1021/acsaelm.3c01161
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-Based Inks for Flexible Supercapacitor Electrodes: A Review

Kiran I. Nargatti,
Tanaya S. Pathak,
Sandeep S. Ahankari
et al.

Abstract: In the world of consumer electronics, flexible and wearable electronic devices have witnessed a remarkable transformation, and flexible supercapacitors (SCs) hold tremendous potential as a power source for these electronic devices. Printing technologies, such as inkjet and screen printing, have emerged as cost-effective and scalable manufacturing techniques for the fabrication of flexible SC electrodes. As a key element of printing technology, ink must have the right balance of conductivity and rheological pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 157 publications
0
6
0
Order By: Relevance
“…The surface-dependent gas-sensing mechanism of the semiconductor materials occurs through the environmental oxygen adsorption on the surface of the sensing element . Depending on the sensor’s temperature, the oxygen molecules reside over it in the form of molecular or atomic species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface-dependent gas-sensing mechanism of the semiconductor materials occurs through the environmental oxygen adsorption on the surface of the sensing element . Depending on the sensor’s temperature, the oxygen molecules reside over it in the form of molecular or atomic species.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Wang et al demonstrated the stable supercapacitor performance of Ni x S y /MoS 2 hybrid nanomaterials with enhanced energy storage capability . Recently, materials such as carbon compounds, transition-metal dichalcogenides, ferromagnetic shape memory alloys, perovskite materials, metal oxides, nitrides, carbides, two-dimensional (2D) conjugated metal–organic frameworks (c-MOFs), etc. have been widely used in various electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…In printing electronics, the thermophysical properties of the ink and the size of the injecting nozzle are key factors in the formation of proper ink droplets with desirable characteristics. The droplet formation criteria is determined by the Z -number, Z = ζ ρ a / μ , a dimensionless parameter in which ζ, ρ, and μ are respectively the surface tension, density, and the dynamic viscosity of the ink solution, and a is the diameter of the injecting nozzle. , A Z -number range of 1 ≤ Z ≤ 14 generally results in good droplet formation and its uniform distribution at the intended regions on the substrate . Inks with Z < 1 or Z > 14 result in elongated ligaments or satellite droplet formation which would result in undesirable printing patterns. , To tune the properties of our ink, we collected the precipitate part of the liquid-phase exfoliated NbS 3 and transferred it to a secondary solvent of 5 mL of isopropyl alcohol (IPA). The solution underwent a 10 min bath sonication for uniform filler dispersion and to prevent filler agglomeration.…”
Section: Ink Preparation and Printed Device Fabricationmentioning
confidence: 99%
“…The water-based rGO/CNF film with optimal CNF content can facilitate efficient electron transport throughout the material and increase hydrophilicity while maintaining the electrical conductivity of the film. This ink can be utilized to produce flexible and scalable electrodes with adjustable morphology and electrochemical performance using a variety of printing methods, including screen, spray, and inkjet printing . As the ink uses water as its main solvent instead of hazardous organic solvents, it is a more environmentally friendly and sustainable option.…”
Section: Introductionmentioning
confidence: 99%
“…This ink can be utilized to produce flexible and scalable electrodes with adjustable morphology and electrochemical performance using a variety of printing methods, including screen, spray, and inkjet printing. 22 As the ink uses water as its main solvent instead of hazardous organic solvents, it is a more environmentally friendly and sustainable option. Consequently, this novel ink paves the way for the development of high-performance, environmentally friendly, and cost-effective supercapacitors with significant potential to transform energy storage in various applications, such as wearable electronics and health monitoring devices.…”
Section: Introductionmentioning
confidence: 99%